Teachers’ perspectives on teaching EFL speaking virtually: A case study of COVID-19 pandemic survival - Butarbutar, Ranta; Leba, Seli Marlina Radja (American Journal of Social Sciences and Humanities, 2023)
The goals of this study are to analyze and provide in-depth detail about how teachers felt and how they taught during the COVID-19 pandemic. The study used a qualitative approach via the Atlas.ti application and used a semi-structured interview to collect data. Five teachers were recruited to answer the research questions to determine what they thought, how they felt, and what they did during the pandemic. To improve the consistency of theme analysis coding (validity or trustworthiness), the study was adjusted based on feedback from external independent reviewers. The results reveal that teaching speaking has a direct effect on four things: (1) the teaching method, (2) the teaching tools, (3) the goals or aims, and (4) how well the students do. As a result, pupils perform better academically, cognitively, and socio-emotionally. This study has flaws, such as the fact that it was conducted in a remote area with few facilities and only used a small sample of teachers with good digital literacy.